PENINGKATAN EKONOMI PETANI DAN KOMUNITAS PETERNAK MELALUI POLA SYIRKAH DI KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Waluyo, Waluyo; Nurohman, Yulfan Arif; Qurniawati, Rina Sari; Waluyo, Alif; Ahzar, Fahri Ali (ABDI MAKARTI, 2024)
The role of farmers in the Indonesian economy is very large, but they have not received the recognition they deserve. Farmers have had the hope of living a prosperous life for a long time, but only a small percentage of farmers live comfortably. Farmers' problems are crop failure and prices are determined by the market, requiring additional income. The habit of farmers on the island of Java is farming and raising livestock, so the community service program offered is improving the economy through raising sheep using the syirkah pattern. The aim is for farmers to get financial improvements and be able to live more prosperously. The community service partners carried out are the people of Kaloran District, Temanggung Regency. The results of this activity enable farmers to raise livestock in a modern way with capital using the syirkah pattern and there is a financial increase for farming families as well as livestock communities